2021
DOI: 10.1002/mpr.1901
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and mental health among at‐risk university students: A prospective study into risk and protective factors

Abstract: Objective:The COVID-19 pandemic has confronted young adults with an unprecedented mental health challenge. Yet, prospective studies examining protective factors are limited. Methods:In the present study, we focused on changes in mental health in a large sample (N = 685) of at-risk university students, which were measured before and during the pandemic. Network modeling was applied to 20 measured variables to explore intercorrelations between mental health factors, and to identify risk and protective factors. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…No study was conducted with medical students and, moreover, the majority analyzed data collected at the beginning of the 2020 COVID-19 pandemic. Two of those studies had results different from ours: mental health problems and stress increased during the first months of the COVID-19 pandemic [ 29 , 30 ]. On the other hand, another study made with university students found no clinically significant changes in mental health symptoms, in line with our study [ 31 ].…”
Section: Discussionmentioning
confidence: 69%
“…No study was conducted with medical students and, moreover, the majority analyzed data collected at the beginning of the 2020 COVID-19 pandemic. Two of those studies had results different from ours: mental health problems and stress increased during the first months of the COVID-19 pandemic [ 29 , 30 ]. On the other hand, another study made with university students found no clinically significant changes in mental health symptoms, in line with our study [ 31 ].…”
Section: Discussionmentioning
confidence: 69%
“…The ongoing coronavirus disease 2019 (COVID-19) pandemic appears to be another challenging phenomenon for college students (5)(6)(7)(8)(9)(10). With the onset of the pandemic, hitherto unknown conditions arose in their lives.…”
Section: Introductionmentioning
confidence: 99%
“…When kids are overly silent and lack communication in class, teachers might detect this circumstance. When mental stress leads to violent student behavior or an increase in suicide attempts, this can lead to out-of-control occurrences (Koelen et al, 2022). As a result, the execution of creative project work will create possibilities for students to cooperate and communicate with teachers and colleagues while it is being implemented.…”
Section: Problem Statementmentioning
confidence: 99%